Prevalence and Risk Factors of Depression Among University Students in Peshawar - Ihsan, Akhoonzada Hamza; Khan, M. Murtaza; Muqarrab Ullah,; Khan, Qaisar Ali; Faizyab,; Khan, Shakir Ullah (Indus Journal of Bioscience Research, 2025)
Introduction: Depression among university students is a significant mental health concern worldwide, with unique stressors such as academic pressures, social challenges, and financial difficulties contributing to its prevalence. This issue is especially pertinent in Peshawar, Pakistan, where students face additional socio-political and cultural challenges, yet there is limited research on the prevalence and risk factors of depression in this population. Objectives: The study aimed to assess the prevalence of depressive symptoms among university students in Peshawar and identify the key risk factors contributing to depression, including academic stress, social isolation, financial pressures, and lifestyle factors. Methodology: A cross-sectional, descriptive research design was used. A sample of 200 full-time university students from various faculties in Peshawar was selected through stratified random sampling. The Patient Health Questionnaire-9 (PHQ-9) was used to assess depressive symptoms, and data were analyzed using SPSS version 25. Findings: The study found a significant prevalence of depressive symptoms among the students. Common symptoms included a lack of interest in activities (35%), feelings of hopelessness (32.5%), sleep disturbances (35%), fatigue (37.5%), and difficulty concentrating (30%). A concerning portion (25%) reported thoughts of self-harm. Despite these symptoms, 60% of students reported no difficulty in managing daily tasks. Discussion: Findings align with global research on academic stress and social isolation impacting students' mental health. Depression is persistent, significantly affecting students’ academic and personal lives, despite many managing daily challenges. Recommendations: Enhance counseling services, implement mental health screenings, establish peer support, reduce stigma, offer crisis interventions, and foster social engagement to reduce isolation.